Vision based persistent localization of a humanoid robot for locomotion tasks - Martínez, Pablo A.; Castelán, Mario; Arechavaleta, Gustavo (Zielona Góra: Uniwersytet Zielonogórski)
Typical monocular localization schemes involve a search for matches between reprojected 3D world points and 2D image features in order to estimate the absolute scale transformation between the camera and the world. Successfully calculating such transformation implies the existence of a good number of 3D points uniformly distributed as reprojected pixels around the image plane.
Keywords: robot localization; monocular vision; humanoid locomotion